Effects of Support Mechanism on the Socio-Emotional Well-Being of Solo Parents - Mendoza, Pearly Joyce (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effects of support mechanisms on the socio-economic well-being of solo parents in Mabitac, Laguna. Using a descriptive research design, the study aimed to assess how various support systems influence the socio-emotional dimensions of self-awareness, self-management, interpersonal skills, and decision-making skills among solo parents. Respondents were profiled according to age, sex, civil status, educational attainment, number of children, occupation, and monthly income. Data were gathered through a structured questionnaire and analyzed using descriptive statistics and inferential tests.Results revealed that most respondents were female, aged 31–40 years, high school graduates, with two to three children, and belonging to the lowest income bracket. The overall composite mean of socio-emotional well-being was 4.11 interpreted as “Often” indicating that support mechanisms consistently influence the well-being of solo parents. Among the indicators self-management ranked highest followed by decision-making skills self-awareness and interpersonal skills. This suggests that support systems significantly help solo parents manage stress improve emotional regulation and strengthen decision-making abilities.Further analysis showed that age and educational attainment serve as predictors of the effects of support mechanisms on socio-emotional well-being particularly in self-awareness and decision-making while sex civil status number of children occupation and income were not significant predictors. These findings highlight the importance of targeted interventions that consider age and educational background in designing support programs.In conclusion support mechanisms positively influence the socio-emotional well-being of solo parents enhancing their capacity to cope with daily challenges and family responsibilities. It is recommended that local government units social workers counselors and community organizations strengthen access to counseling services financial literacy programs and peer support groups. Such interventions may further improve emotional resilience and social functioning among solo parents. The proposed action plan may be implemented to ensure sustainability and continuous improvement of support mechanisms in local communities and stakeholders engagement.